Formulation-Dependent Extrudability of Highly Filled Alginate System for Vaginal Drug Delivery - Arianna Chiappa; Alice Fusari; Marco Uboldi; Fabiana Cavarzan; Paola Petrini; Lucia Zema; Alice Melocchi; Francesco Briatico Vangosa (Gels)
The incorporation of solid particles as a filler to a hydrogel is a strategy to modulate its properties for specific applications, or even to introduce new functionalities to the hydrogel itself. The efficacy of such a modification depends on the filler content and its interaction with the hydrogel matrix. In drug delivery applications, solid particles can be added to hydrogels to improve drug loading capacity, enable the inclusion of poorly soluble drugs, and modulate release kinetics. This work focuses on the case of alginate (ALG)-based hydrogels, obtained following an internal gelation procedure using CaCO3 as the Ca2+ source and containing a high solid volume fraction (up to 50%) of metronidazole (MTZ), a drug with low water solubility, as a potential extrusion-based drug delivery system. The impact of the hydrogel precursor composition (ALG and MTZ content) on the rheological behavior of the filled hydrogel and precursor suspension were investigated, as well as the hydrogel stability and MTZ dissolution. In the absence of solid MTZ, the precursor solutions showed a slightly shear thinning behavior, more accentuated with the increase in ALG concentration. The addition of drugs exceeding the saturation concentration in the precursor suspension resulted in a substantial increase (about one order of magnitude) in the low-shear viscosity and, for the highest MTZ loadings, a yield stress. Despite the significant changes, precursor formulations retained their extrudability, as confirmed by both numerical estimates and experimental validation. MTZ particles did not affect the crosslinking of the precursors to form the hydrogel, but they did control its viscoelastic behavior. In unfilled hydrogels, the ALG concentration controls stability (from 70 h for the lowest concentration to 650 h for the highest) upon immersion in acetate buffer at pH 4.5, determining the MTZ release/hydrogel dissolution behavior. The correlations between composition and material properties offer a basis for building predictive models for fine-tuning their composition of highly filled hydrogel systems.